Strain dependence of Berry-phase-induced anomalous Hall effect in the non-collinear antiferro-magnet Mn3NiN - Johnson,F; Boldrin,D; Zemen,J; Pesquera,D; Kim,J; Moya,X; Zhang,H; Singh,HK; Samathrakis,I; Cohen,L (Applied Physics Letters, 2021)
The anomalous Hall effect (AHE) has been shown to be present in certain non-collinear antiferromagnets due to their symmetry-breaking magnetic structure, and its magnitude is dependent primarily on the non-zero components of the Berry curvature. In the non-collinear antiferromagnet Mn3NiN, the Berry phase contribution has been predicted to have strong strain dependence, although in practice, direct observation may be obscured by other strain-related influences—for instance, magnetic phase transitions mediated by strain. To unravel the various contributions, we examine the thickness and temperature dependence of the AHE for films grown on the piezoelectric substrate BaTiO3. We observe a systematic reduction in TN due to increased compressive strain as film thickness is reduced and a linear decrease in the AHE magnitude as the films are cooled from their ferrimagnetic phase above TN to their antiferromagnetic phase below. At 190 K, we applied an electric field across a 0.5 mm thick BaTiO3 substrate with a 50 nm thick Mn3NiN film grown on top and we demonstrate that at the coercive field of the piezoelectric substrate, the tensile in-plane strain is estimated to be of the order of 0.15%, producing a 20% change in AHE. Furthermore, we show that this change is, indeed, dominated by the intrinsic strain dependence of the Berry curvature.